Preoperative Mean Platelet Volume and Platelet Distribution Width Predict Postoperative Sepsis in Patients with Colorectal Cancer. (30th October 2019) - Li, Xue-ting; Yan, Zibo; Wang, Rui-tao; Yu, Kai-jiang
Abstract : Purpose . Mean platelet volume (MPV) and platelet distribution width (PDW) have been used to reflect the platelet activity in clinics. We assessed initial serum MPV and PDW levels in colorectal cancer (CRC) patients, in predicting the development of sepsis in CRC patients postoperatively. Patients and Methods . This study included 220 patients diagnosed with CRC. 55 patients were stratified to one group that developed sepsis postoperatively, and 165 patients were stratified to the other group that did not develop sepsis postoperatively. Clinical and laboratory characteristics were collected 3 days before the operation. Results . MPV (p < 0.001 ) was significantly higher and PDW (p < 0.001 ) was significantly lower in the sepsis group than in the nonsepsis group. Either MPV or PDW is independently associated with ICU mortality in sepsis patients with CRC. MPV is independently associated with 14-day, 28-day, and 90-day mortality and PDW is independently associated with 90-day mortality in patients with CRC. The prevalence of sepsis increased as MPV tertiles increased (p < 0.001 ), and the prevalence of sepsis increased as PDW tertiles decreased (p < 0.001 ). Conclusions . Serum MPV and PDW levels between CRC patients with/without sepsis postoperatively are significantly different. The initial serum MPV or PDW levels can potentially serve as a predictor of sepsis in CRC patients postoperatively.